Sustainability Literacy to Vocational Students through Distance Learning with Experimental Demonstration: Ionic Liquid Experiment and Its Application as Fire Retardant - Afifah, Sakhiyyah; Mudzakir, Ahmad; Nandiyanto, Asep Bayu Dani; Ragadhita, Risti; Maryanti, Rina; Al Husaeni, Dwi Fitria; Al Husaeni, Dwi Novia; Fiandini, Meli (Journal of Technical Education and Training, 2023)
The purpose of this study is to introduce sustainability literacy to vocational students through distance learning with experimental demonstration as well as show the production process of ionic liquid and its application as a fire-retardant agent. The method was the implementation of distance learning with an experimental demonstration method to 40 vocational students through three stages, namely given a pre-test; given an instructional video, and given a post-test. The learning process carried out was assisted by a learning video containing basic theory, experiments, and the application of ionic liquids. In this case, we taught the concept of manufacturing ionic liquid and its application in the industrial world that will be useful for vocational students when they graduate. The results showed that the experimental demonstration method succeeded in improving student learning outcomes because of an increase in the score between the pre-test and post-test scores. This success is because students are taught through unique learning media such as a learning video. This learning video succeeded in increasing students’ understanding because the information in the video was presented attractively to stimulate students’ curiosity and interest in the subject. In addition, students’ responses to the learning video were that they became more enthusiastic about learning because the content delivered relates to the vocational training that they are learning, the video display is attractive, and the videos are easily accessible. Furthermore, the impact of the learning video on industrial applications is that the information conveyed in the video can be an alternative to making environmentally friendly solvents and solutions to improve the quality of bamboo as one of the materials used in industry. The addition of an experimental demonstration using commercially available materials also attracts students more because it motivates them to try it themselves. This study shows that experimental demonstration is effectively used in learning and fosters sustainability values in students.